Implementation of Cooperative Learning Models of Numbered Heads Together Method for Improving Skills in Forming for Early Age Children in PAUD Rosellana - Octaviani, Sinta Rahayu; Windiarti, Rina (Jurusan PGPAUD FIP UNNES, 2021)
Every child has the skills to form in theirs. Increasing forming skills in children requires stimulation by giving the opportunity to be more creative. Therefore forming skills are very appropriate to be developed from an early age. One way that can be done to improve the skills of forming early childhood is that the cooperative learning method, Numbered Head Together (NHT) is expected to be able to assist children in developing forming skills. The researcher aimed to find out the differences and improvement of skills in forming early childhood based on the implementation of Numbered Head Together learning in Paud Rosellana.This research is a quantitative research using the One-Group Pretest-Posttest Design method. Data collection techniques in this study used scale forming skills in early childhood, while data analysis used the Paired Sample t-Test method and percentage techniques. Based on the results of the statistical test of hypothesis testing, the t-test test data using the Paired Sample t-Test on the SPSS program obtained t count > t table that is (8,447> 2,045), the sig (2-tailed) value was 0,000, so Ha was accepted and HO was rejected . Based on this, it can be concluded that there is a significant difference in the skills of forming early childhood after being treated using the Numbered Head Together cooperative learning model.